Assessing Heavy Metal Contamination in Parts of Middle Benue Trough, Central Nigeria: Implications for Public Health and Environmental Safety (Journal of Pure and Applied Sciences (Science Forum), 2025)
Assessment of soil and water quality is critical for effective environmental management, particularly in regions impacted by human activities such as agriculture, mining, and industrial development. This study investigated the extent and environmental implications of heavy metal contamination in soils from Faya and its surrounding areas, located within the Middle Benue Trough of Central Nigeria. A total of thirty-three soil samples were collected from areas underlain by Shale, Limestone, Black Shales, Sandstone, and Migmatite formations. These samples were analyzed for concentrations of arsenic (As), lead (Pb), copper (Cu), chromium (Cr), manganese (Mn), cadmium (Cd), cobalt (Co), selenium (Se), zinc (Zn), and barium (Ba). To assess the level and potential sources of contamination, a suite of pollution indices was applied, including the Contamination Factor (CF), Pollution Load Index (PLI), Enrichment Factor (EF), and Geoaccumulation Index (Igeo). Results revealed elevated concentrations of As (mean: 28.10 mg/kg), Cd (25.68 mg/kg), Se (6.75 mg/kg), and Pb (16.93 mg/kg), frequently exceeding guideline limits set by the World Health Organization (WHO) and those proposed by Kabata-Pendias and Pendias (1999, 2001). High CF and EF values for As, Cd, Se, and Co suggest strong anthropogenic influences, likely linked to agricultural runoff, mining operations, and industrial discharges. Notably, samples RMP01A, RMP08B, and RMP012A exhibited the highest PLI values (PLI > 1), indicating cumulative pollution in these locations. In contrast, elements such as Mn, Ba, and Zn were generally within acceptable limits. The Igeo assessment further identified Cd and Se as the most concerning contaminants, with several samples classified as “moderately to heavily polluted,” posing substantial ecological and public health risks. This study underscores significant environmental and health hazards in the region and emphasizes the urgent need for policy-driven remediation strategies and sustainable land use practices.